PENGARUH INSENTIF DAN LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA MAHASISWA KERJA PRAKTIK (Studi Kasus Mahasiswa Angkatan 2020 Pada Salah Satu Kampus Di Jakarta) - Nisa, Rifka; Murti, Arif (MEDIA RISET EKONOMI [MR.EKO], 2024)
There is increasingly fierce competition in the world of work so that the number of unemployment that occurs at this time is still relatively high when compared to before the pandemic. In an effort to deal with this problem, the development of an independent campus education program is carried out in order to create students who are professional and ready to enter the world of work actually. Similarly, Pertamina University does this, namely by holding a Practical Work program, as for in carrying out this Practical Work program, students are required to be able to commit to related agencies during the implementation of Practical Work. But in fact, there are still many students who carry out practical work programs solely as a fulfillment of credits as a graduation requirement. This study aims to determine the effect of incentives on work motivation and the influence of the work environment on work motivation. In addition, this study also aims to determine the effect of incentives and work environment on the work motivation of practical work students class of 2020 Pertamina University. The form of research used is causal associative with a quantitative approach. This study used a sample of 306 students with a simple random sampling technique with convenience sampling. The method used in this study was multiple linear regression through SPSS 26 software. The results of this study showed that partially incentives did not have a significant effect on work motivation and the work environment partially had a significant effect on work motivation. In addition, simultaneously incentives and work environment have a significant influence on work motivation.